Effect of self-monitoring of blood pressure on blood pressure control in pregnant individuals with chronic or gestational hypertension: the BUMP 2 randomized trial - Chappell, LC; Tucker, KL; Galal, U; Yu, L-M; Campbell, H; Rivero-Arias, O; Allen, J; Band, R; Chisholm, A; Crawford, C; Dougall, G; Engonidou, L; et al. (American Medical Association, 2022)
Importance Inadequate management of elevated blood pressure is a significant contributing factor to maternal deaths. The role of blood pressure self-monitoring in pregnancy in improving clinical outcomes for the pregnant individual and infant is unclear.